2017
DOI: 10.1007/s11524-016-0110-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Utilization and Cost of Health Services between Veterans Experiencing Brief and Ongoing Episodes of Housing Instability

Abstract: Housing instability is associated with costly patterns of health and behavioral health service use. However, little prior research has examined patterns of service use associated with higher costs among those experiencing ongoing housing instability. To address this gap, we compared inpatient and outpatient medical and behavioral health service utilization and costs between veterans experiencing brief and ongoing episodes of housing instability. We used data from a brief screening instrument for homelessness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Finally, Byrne et al. () used data from the universal homelessness screening protocol administered in the VA to distinguish between Veterans experiencing brief and ongoing episodes of housing instability; those whose housing instability was ongoing incurred $7,573 greater VA health care costs than those with brief episodes (Byrne et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, Byrne et al. () used data from the universal homelessness screening protocol administered in the VA to distinguish between Veterans experiencing brief and ongoing episodes of housing instability; those whose housing instability was ongoing incurred $7,573 greater VA health care costs than those with brief episodes (Byrne et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, they found that homelessness was associated with substantial increases in outpatient encounters, emergency department visits, and inpatient admissions ). Finally, Byrne et al (2017) used data from the universal homelessness screening protocol administered in the VA to distinguish between Veterans experiencing brief and ongoing episodes of housing instability; those whose housing instability was ongoing incurred $7,573 greater VA health care costs than those with brief episodes (Byrne et al 2017). Because this universal screening protocol was introduced in the VA in October 2012, after the timeframe of our study, these data were not available for us to identify Veterans with housing instability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations